Pengaruh Suku Bunga, Inflasi, dan Pertumbuhan PDB Terhadap Return Saham Sektor Barang Baku Indeks LQ45 Periode 2020-2024 - Hanum Ahsibna Maudiyah; Annisa Alifa Ramadhani (Warmadewa Economic Development Journal (WEDJ), 2025)
Macroeconomic factors have a role in influencing stock performance, resulting in stock market fluctuations during the pandemic and post-Covid-19 pandemic. The purpose of this research is to analyze the effect of interest rates, inflation, and GDP growth on stock returns in the raw goods sector in the LQ45 Index for the 2020-2024 period. The method used is a quantitative approach with secondary data analyzed using a panel data regression model. The population of this study were 117 raw goods sector stocks listed on the Indonesia Stock Exchange (IDX) with a research sample of 8 companies. The results showed that partially, the interest rate and GDP growth variables had a negative and significant effect, while the inflation variable had no effect on stock returns. Simultaneously, interest rates, inflation, and GDP growth affect the stock returns of the raw goods sector. These findings imply that investors need to consider macroeconomic indicators as a whole in making investment decisions.